2021
DOI: 10.3389/fphar.2021.667282
|View full text |Cite
|
Sign up to set email alerts
|

Selective Wnt/β-Catenin Pathway Activation Concomitant With Sustained Overexpression of miR-21 is Responsible for Aristolochic Acid-Induced AKI-to-CKD Transition

Abstract: Acute kidney injury (AKI) is increasingly recognized as a cumulative risk factor for chronic kidney disease (CKD) progression. However, the underlying mechanisms remain unclear. Using an aristolochic acid (AA)-induced mouse model of AKI-to-CKD transition, we found that the development of tubulointerstitial fibrosis following AKI was accompanied with a strong activation of miR-21 and canonical Wnt signaling, whereas inhibition of miR-21 or selective silencing of Wnt ligands partially attenuated AKI-to-CKD trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, no data to date are available about the mechanism of IKKα on inducing kidney fibrosis. As is known that Wnt/β‐catenin pathway is involved in kidney fibrosis [37–45], our studies found active‐β‐catenin and snail were markedly increased in UIRI and UUO models which were down‐regulated when IKKα was knocked out, indicating that knockout of IKKα gene inhibits activation of wnt/β‐catenin pathway. In addition, the binding of IKKα and β‐catenin was studied in vitro.…”
Section: Discussionmentioning
confidence: 61%
“…However, no data to date are available about the mechanism of IKKα on inducing kidney fibrosis. As is known that Wnt/β‐catenin pathway is involved in kidney fibrosis [37–45], our studies found active‐β‐catenin and snail were markedly increased in UIRI and UUO models which were down‐regulated when IKKα was knocked out, indicating that knockout of IKKα gene inhibits activation of wnt/β‐catenin pathway. In addition, the binding of IKKα and β‐catenin was studied in vitro.…”
Section: Discussionmentioning
confidence: 61%
“…A moderate increase in Wnt/β-catenin signaling is beneficial, but excessive activation of this pathway could trigger renal fibrosis (Guo et al, 2019;Sun et al, 2020). In addition, early intervention, but not late with β-catenin inhibitor significantly attenuates the apoptosis and inflammation induced by aristolochic acid (AA) (Kuang et al, 2021). Therefore, the dual role of Wnt/β-catenin signaling in CKD needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The development of AKI-to-CKD is heterogeneous as this transition occurs in different patients and can be caused by multiple conditions, such as nephrotoxin, sepsis, ischemia-reperfusion, surgical operation, and cardiovascular diseases. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…[2] The development of AKI-to-CKD is heterogeneous as this transition occurs in different patients and can be caused by multiple conditions, such as nephrotoxin, sepsis, ischemia-reperfusion, surgical operation, and cardiovascular diseases. [3] Currently, the mechanism of this multifactorial process remains unclear. However, such information is crucial for developing treatment strategies to prevent the harmful progression of kidney injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation